Polymorphism of Myostatin (MSTN) Promoter Gene and its Association with Growth and Muscling Traits in Bali Cattle - Himmatul Khasanah; A. Gunawan; R. Priyanto; M. F. Ulum; Jakaria Jakaria (Media Peternakan, 2016)
Myostatin (MSTN) gene plays a key role in skletal muscle homeostasis such as inducing muscle athrophy, poliferation of myoblast, increasing ubiquitin-proteasomal, downregulating IGF pathway, and glucolysis. Myostatin gene expression is controled by CpG island located in promoter region. The objectives of this research were to identify polymorphism of MSTN promoter gene and to associate the polymorphism of SNP with growth and muscling traits in Bali cattle. A total of 48 Bali cattle from BPTU-HMT Bali island was screened to identify genetic polymorphisms in MSTN promoter region using sequencing method. The growth and muscling traits were measured at 12 months of age. The muscling traits were evaluated using ultrasound console with linear transducer having frequency 6.5 Hz and scaning we conducted at 130 mm in deep. Analysis of polymorphism was conducted by using PopGen 1.32 software. The association of MSTN with growth and muscling traits were analyzed by using General Linear Model (GLM) procedure. This result showed that a total of 20 polymorphic SNPs (seven SNPs in CpG island) were detected in this region. Although, only 3 SNPs (g.-8078C>T, g.-7996G>C, and g.-7930A>G) had equilibrium condition in Hardy-Weinberg analysis. The association result showed that 2 SNPs (g.-7799T>C and g.-7941C>T) were significantly associated with intramuscular fat percentage (P≤0.05) in Bali cattle. Although the 2 SNPs were nominally significant at nominal P≤0.05 threshold, they were not significant after Bonferroni correction for multiple testing. It could be concluded that MSTN promoter gene was polymorphic in Bali cattle and there were 2 SNPs associated with carcass quality.